Elucidation of Apigenin Derivatives from Ethyl Acetate Fraction of Stachys byzantina with Potent Antioxidant and Anti-Staphylococcus aureus Properties - Mostafa Pirali Hamedani; Farzaneh Aram; Abbas Hadjiakhoondi; Nasrin Samadi; Saeed Tavakoli; Fatemeh Kiashi; Saied Goodarzi; Zahra Tofighi (Tehran University of Medical Sciences, 2023)
The Stachys genus is a medicinal plant, with 34 different species, from Lamiaceae family that grows in Irano-Anatolian plateau. There are 12 species of Stachys native to Iran. Some species of Stachys have been used in traditional medicine of Iran, Turkey, Italy, Greece, China, and Japan for the treatment of various diseases like inflammation, common cold, and etc. Some researchers have noted many biological effects, such as cytotoxic, antioxidant, immunomodulator, anti-inflammatory and anti-bacterial effects for the members of this genus. There are a few evidences on phytochemical constituents of S. byzanthinaThe aim of this study was phytochemical investigation of various extracts of this plant to obtain the most efficient fractions and compound(s) to study the antimicrobial effects of this plant. Separation and isolation of compounds was performed by various methods of chromatography. The structure of each compound was identified by spectroscopic methods.Antimicrobial studies were performed on different fractions of S. byzantina by microdilution method and to determine the Minimum Inhibitory Concentration (MIC), agar well diffusion was done.Ethyl acetate fraction has the highest total phenol contents (1082.05 mg GAE/g fraction) and antioxidant capacity (IC50= 1.23 mg/ml). Also, ethyl acetate fraction, the most potential fraction of S. byzanthina, was demonstrated the largest inhibition zone (17.5 ± 0.7 mm) with 5 mg/ml in MIC against Staphylococcus auresus.Apigenin and its derivatives were isolated from this fraction and according to literature; they can be responsible for antibacterial activity of this fraction of S. byzanthina.